Consensus Statements on Driving in People with Parkinson's Disease. Issue 2 (3rd April 2014) - Classen, Sherrilene
ABSTRACT: Parkinson's disease (PD) is a complex neurodegenerative disorder leading to motor and non-motor impairments, all of which can affect fitness to drive. The literature suggest that on-road and simulated driving performances are impaired in people with PD, as compared to healthy control drivers. Clear associations exist between impaired driving performance and contrast sensitivity, visual processing speed, and psychomotor speed. Prior to this review and expert panel process, no evidence-based guidelines have existed to help occupational therapy practitioners determining fitness to drive in those with PD. Three consensus statements are presented in this work to enable occupational therapy practitioners and other driver rehabilitation specialists to make fitness to drive determinations in people with PD.